Soft-tissue simulation of the breast for intraoperative navigation and fusion of preoperative planning - Alcañiz, Patricia; Vivo de Catarina, César; Gutiérrez, Alessandro; Pérez, Jesús; Illana, Carlos; Pinar, Beatriz; Otaduy, Miguel A. (Frontiers in Bioengineering and Biotechnology, 2022)
Computational preoperative planning offers the opportunity to reduce surgery time and patient risk. However, on soft tissues such as the breast, deviations between the preoperative and intraoperative settings largely limit the applicability of preoperative planning. In this work, we propose a high-performance accurate simulation model of the breast, to fuse preoperative information with the intraoperative deformation setting. Our simulation method encompasses three major elements: high-quality finite-element modeling (FEM), efficient handling of anatomical couplings for high-performance computation, and personalized parameter estimation from surface scans. We show the applicability of our method on two problems: (i) transforming high-quality preoperative scans to the intraoperative setting for fusion of preoperative planning data, and (ii) real-time tracking of breast tumors for navigation during intraoperative radiotherapy. We have validated our methodology on a test cohort of 9 patients who underwent tumor resection surgery and intraoperative radiotherapy, and we have quantitatively compared simulation results to intraoperative scans. The accuracy of our simulation results suggest clinical viability of the proposed methodology.